Soot-on-snow experiment: artificial deposition of light-absorbing particles onto snow surfaces in 2018 - Svensson, Jonas; Leppänen, Leena; Hannula, Henna-Reetta; Kontu, Anna; Shen, Yi-cheng; Meinander, Outi; Dagsson-Waldhauserová, Pavla; Mesceriakovas, Arunas; Heikkinen, Enna; Ruppel, Meri; Sippula, Olli; Ström, Johan; et al. (Frontiers in Earth Science, 2024)
The absorption of shortwave irradiance in snow depends on the physical properties of snow (e.g. snow grain size and shape, liquid water content, etc.) and light-absorbing particles (LAP). Originating from natural and anthropogenic sources, LAP has been reported to accelerate snowmelt significantly in different regions globally. Yet, our process-level understanding of LAP after deposition onto snow remains rather limited.Here we investigate the impacts of artificial deposition of different LAP onto snow surfaces in an outdoor environment of northern Finland. Following LAP dry deposition into a custom-made tent standing on top of the snowpack, the albedo was followed along with the properties of snow in snow pit measurements throughout the spring season. The results showed that the albedo decay at the end of the season for the different spots were linked to the initial amount and type of LAP that were deposited onto the snowpack. Measured snow temperature profiles from LAP doped snow versus natural reference snow illustrated that the LAP affected snow had higher temperatures in the subsurface snow layers. Collected snow samples analyzed for size distribution of soot particles revealed no apparent agglomeration of soot particles during thaw-freezing events taking place during the experiment. Despite the relatively large perturbation of the experimentally deposited LAP, their impact on the season length was only up to three days. Additional experiments are, nevertheless, needed to better constrain the effects of LAP on snow albedo, melt rate, and other associated processes.